The Effect of Audit Fees and Auditor Professionalism on Audit Quality with Remote Auditing as A Mediating Variable (Empirical Study of Auditors in the Province of Banten 2022-2023) - Afda, Syifa Nurul; Muhamad, Taqi; Denny, Susanto (Accounting and Sustainability, 2024)
The study aims to determine the effect audit fees and auditor professionalism on audit quality with remote auditing as a mediating variable. This research method uses quantitative methods. This research uses primary data by collecting data using a questionnaire. The sample of this research are auditors who work in Public Accounting Firms Banten Province. The sample technique used in this research is Purposive Sampling method with a total sample of 50 research data. The data analysis technique for this study used multiple regression analysis with Statistical Package For the Social Sciences Software (SPSS v27) and Path Analysis with the help of an online Spbel Calculator. The result of this study prove that audit fees have a significant positive effect on audit quality, auditor professionalism has a positive effect on audit quality, remote audits have a negative effect on audit quality, audit fees have a positive effect on remote audits, and auditor professionalism has a positive effect on remote audits. Behind that, remote audits are not able to act as a mediator on the effect of audit fees on audit quality. But, remote audits is able to act as a mediator on the effect of auditor professionalism on audit quality.